(untitled) (Confluenţe Bibliologice, 2025)
The article renders with a life and activity of a famous Russian librarian Margarita Ivanovna Rudomino, the founder and the leader for half a century of Russian State Library for Foreign Literature. She created and developed the collection of documents in main European languages. Today, the Library oﬀers a unique collection of foreign literature numbering about 4.4 million copies, including books and periodicals in more than 140 languages. In the composition of the foreign editions of prime importance is the rich collection in the world of classical and contemporary literature in the original language, in particular in English, French, German and Spanish. Nearly 1.9 million copies, also, represent foreign editions in literary studies and linguistics, including in the methodology of teaching languages, books in foreign art and art history, historical works and studies the World Biographical Archive.